Does psychic numbing apply to endangered species conservation? The case of the Peregrine Falcon in Berkeley, California - Boren, Alexandra; Echeverri, Alejandra (Frontiers in Conservation Science, 2025)
IntroductionMany individuals exhibit compassion towards charismatic animals in distress, yet they are not as motivated to help the thousands of endangered animal species. The foundation of this paradox is psychic numbing, a psychological phenomenon that explains why people are more inclined to donate to help save human lives when presented with accounts of single identifiable victims compared to accounts of mass atrocities like genocide. The impact of psychic numbing on human tragedies has been well documented, but its impact on non-human tragedies, such as the crisis of endangered species conservation, has not been thoroughly assessed.MethodsThis study uses Peregrine Falcon (Falco peregrinus) conservation as a case study, examining whether identifiable lives or statistical lives elicit the greatest concern for Peregrine Falcon preservation and increased donations. Participants are randomly presented with one of three messages: (1) The story of Annie, a celebrity falcon residing in the University of California, Berkeley, (2) Statistical data on Peregrine Falcon decline and history, or (3) A combination of Annie’s story and statistical data.ResultsWe did not find a significant difference in donation amount for identifiable versus statistical lives. However, the three different messaging conditions did evoke significant differences in word association tasks about endangered species.DiscussionOur results demonstrate the importance of further research into messaging conditions that will bring about the greatest level of human action for endangered species conservation.